PERAN PENDAMPING DESA DALAM PEMBERDAYAAN MASYARAKAT - Faizal, Faizal (KOMUNIKA, 2018)
Development strategies using top-down approaches have an impact on: First, the loss of public confidence in the government. Second, it does not provide opportunities and opportunities for the community to participate in development programs. Third, low public participation in maintaining the results of development.  To that end, the development approach that is offered is a buttam up approach, that is development by utilizing the resources and local wisdom or known as community empowerment. Parties who have competence in building awareness of their potential, motivate, and guide the community in developing the existing potential is the Facilitator or Village Assistant. The problem is that the Facilitator or Village Assistant has been appointed by the government, but the level of community participation in development is relatively low. Therefore, it should be questioned about the role of village facilitators or facilitators in community empowerment, and on the competencies of village facilitators or facilitators.To answer the research questions the researchers determined a sample of 374 pupulations with snow ball sampling technique using interview method, observation, and documentation in data collection. The data that have been collected will be analyzed by analytical content method then using inductive and deductive thinking method in taking conclusion. The results show that Mulang Maya Village Assistant only performs mentoring role and technical facilitation role which is administrative characteristic, such as facilitation and facilitation in arrangement of work program, preparation of financial accountability report, and supervision of physical construction implementation (inprastruktrur). Efforts to melt away with the community, provide motivation, and utilization of human resources in addition to village government apparatus, the use of natural resources, and social resources has not been done. Meanwhile, the competence of facilitators or village facilitators, such as general competence, core competencies, and core competencies supported by academic and social capacities are not sufficient. The Facilitator or Assistant of Mulang Maya Village has a high school academic capacity and technical administration experience